Developing Small Business Through Character with the Application of Mind Mapping On Aisyiyah Entrepreneur - Rina Mudjiyanti; Rezky Pramunindra; Ani Kusbandiyah; Irawan Randikaparsa; Rifka Utami Arofah (Journal of Society, Community and Business Development, 2023)
Small businesses have grown rapidly, but that does not mean without obstacles. The growth and development of small businesses can improve an independent economy, but it needs to be supported by the mentality and character of an entrepreneur. Business owners must be able to carry out good management in various economic conditions that are full of uncertainties. Perseverance and mental toughness as well as a positive mindset play an important role in being able to develop strategies to compete and survive, as well as to develop even better. Good planning is done so that an entrepreneur more structured in the process of starting or developing a business, as well as more measurable expectations take action to minimize losses. The target of this activity is Aisyiyah entrepreneur in the Banyumas area. The method used, with providing business development training to participants, builds character and mentality by applying entrepreneurial mind mapping. Business owners have the ability to find solutions to every problem with the right strategy. it is hoped that by having a positive character and mentality, make a mind map in developing business strategies that can improve and develop Aisyiyah's small businesses in the Banyumas area. Keywords: Mind mapping, Caracter, Creativity, Aisyiyah.